Certain pMMR colorectal cancer patients should undergo additional MSI-PCR testing to reduce the risk of misdiagnosing MSI-H and Lynch syndrome - Jinglin Huang; Liang Xu; Yacheng Cai; Xiaoli Tan; Hanjie Lin; Zhiting Chen; Chao Wang; Weihao Deng; Xinhui Fu (BMC Cancer)
Abstract Background Microsatellite instability (MSI) status guides immunotherapy and Lynch syndrome (LS) screening. Given the 5–10% discordance rate between mismatch repair immunohistochemistry (MMR-IHC) and Microsatellite instability polymerase chain reaction (MSI-PCR), true high microsatellite instability (MSI-H) cases in proficient mismatch repair (pMMR) colorectal cancer (CRC) may miss critical interventions. This study investigates molecular pathological characteristics between concordant and discordant groups assessed by these two methods, aiming to reduce the risk of misdiagnosing MSI-H and LS. Methods The MMR-IHC and MSI-PCR were conducted respectively in 2910 CRC patients. Sanger sequencing identified the mutation status of KRAS, BRAF, and PIK3CA genes, and next-generation sequencing (NGS) detected LS-related genes. We compared the molecular pathological features between the pMMR&MSS and pMMR&MSI-H groups, as well as between the dMMR&MSI-H and dMMR&MSS groups. Eleven screening strategies for pMMR&MSI-H were formulated for pMMR patients. Results The consistency rate between the two methods was 96.8% (2816/2910), with a discordance rate of 3.2% (94/2910), comprising 43 cases in the pMMR&MSI-H group and 51 cases in the dMMR&MSS group. Germline mutations in LS-associated genes were detected in 36.4% (4/11) of the pMMR&MSI-H group but were absent in all 9 dMMR&MSS cases. Compared with the pMMR&MSS consistent group, the pMMR&MSI-H inconsistent group showed higher prevalence in patients with right colon (55.8% vs.20.3%), well-differentiated (18.8% vs.8.4%), and PIK3CA exon 20 (E20) mutations (30.0% vs.8.7%). Compared with the dMMR&MSI-H consistent group, the dMMR&MSS inconsistent group was more common in patients with rectum (49.0% vs. 15.2%), stage IV patients (23.5% vs. 8.3%), and PIK3CA E20 wild-type (97.8% vs. 82.4%). The strategy of supplemental MSI-PCR detection for the right colon pMMR patients could identify 55.8% (24/43) of pMMR&MSI-H patients. Adding the detection of patients with PIK3CA E20 mutation based on the right colon can increase the PMMR&MSI-H detection rate to 65.1% (28/43). Conclusion We recommend supplemental MSI-PCR testing for pMMR CRC patients with right colon OR PIK3CA E20 mutation. For those with MSI-H results, subsequent NGS should be performed to identify germline mutations in LS-associated genes.